A New Method to Study Blood Pressure, Heart Rate and EEG as a Function of Reaction Time - Värri, A. O.; Grote, L.; Penzel, T.; Cassel, W.; Peter, J. H.; Hasan, J. (Methods of Information in Medicine, 1994)
A new method is presented to study the relationship between reaction time and blood pressure, heart rate and EEG. The method consists of a simultaneous recording of continuous invasive or non-invasive arterial blood pressure, ECG, EEG, EMG and EOG in a sound-isolated chamber while a monotonous visual reaction time test is running for about 90 minutes. The signals are A/D-converted and analyzed digitally after recording. One second average amplitudes are computed. Systolic, mean and diastolic blood pressure values are calculated, and the EEG is divided into the delta, theta, alpha, sigma and beta frequency bands. The signal amplitudes are averaged in three different reaction time categories, i. e., when the reaction is normal, delayed or missing. Preliminary tests suggest that interesting differences can be observed in the studied variables in different reaction time classes. This method can also be applied to the investigation of autonomic control and to treatment studies.
Keywords: Vigilance; Cardiovascular Responses; Blood Pressure; EEG Responses; Biosignal Processing